Polarization characteristics and attraction efficiency of conventional canopy traps and a new trap based on tabanid polarotaxis - Blahó, Miklós (JOURNAL OF LANDSCAPE ECOLOGY, 2009)
Tabanid flies can cause severe problems for humans and animals because of the diseases vectored by the haematophagous females when sucking blood from vertebrates. To catch tabanids, several different traps have been developed, many of them attracting tabanids visually by shiny black objects and/or surfaces. It is believed that such black structures may imitate the dark silhouette of the host animal, and their flapping in the wind might mimic the motion of the host. Although the most frequently used visual target is a shiny black ball, the reason for its attractivity is unclear. If the exact cause(s) of this attractivity could be revealed, the attraction of the visual target of tabanid traps could be improved. The recent discovery of positive polarotaxis (i.e. attraction to horizontally polarized light) in tabanids puts the phenomenon in a new light. This polarotactic behaviour can be used to develop new tabanid traps. Based on our observation that tabanids are attracted to horizontal polished black gravestones, we present here a new polarization canopy trap. The visual target of the new trap is a horizontal shiny black disk with a narrow shiny black skirt near the ground level. Using videopolarimetry, we measured the reflection-polarization characteristics of this new visual target, and compared them with those of a shiny black sphere and torus. In choice experiments in the field we demonstrated that our new visual target is much more attractive to tabanids than the black sphere and torus. We showed that the reason for the very high attractiveness of the new visual target is that it reflects much larger amount of horizontally polarized light than the conventional black target ball. We also measured and compared the reflection-polarization characteristics of small-scale models of some conventional canopy traps. Taking into consideration the amount of horizontally polarized light reflected from these traps, we revisited the causes of their attraction to tabanids.